2012
DOI: 10.1104/pp.112.198457
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Halogenated Auxin, 4-Chloroindole-3-Acetic Acid    

Abstract: Seeds of several agriculturally important legumes are rich sources of the only halogenated plant hormone, 4-chloroindole-3-acetic acid. However, the biosynthesis of this auxin is poorly understood. Here, we show that in pea (Pisum sativum) seeds, 4-chloroindole-3-acetic acid is synthesized via the novel intermediate 4-chloroindole-3-pyruvic acid, which is produced from 4-chlorotryptophan by two aminotransferases, TRYPTOPHAN AMINOTRANSFERASE RELATED1 and TRYPTOPHAN AMINOTRANSFERASE RELATED2. We characterize a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 27 publications
5
102
0
1
Order By: Relevance
“…2 However, a second bioactive auxin, 4-Cl-IAA, predominates during the later stages of seed development. Metabolism experiments demonstrate that the chlorine is not introduced after the formation of IAA, and it was therefore of paramount importance to determine whether the pea aminotransferases can also utilize 4-chlorotryptophan.…”
Section: A Mutation Affecting the Synthesis Of 4-chloroindole-3-acetimentioning
confidence: 99%
See 3 more Smart Citations
“…2 However, a second bioactive auxin, 4-Cl-IAA, predominates during the later stages of seed development. Metabolism experiments demonstrate that the chlorine is not introduced after the formation of IAA, and it was therefore of paramount importance to determine whether the pea aminotransferases can also utilize 4-chlorotryptophan.…”
Section: A Mutation Affecting the Synthesis Of 4-chloroindole-3-acetimentioning
confidence: 99%
“…Metabolism experiments also ruled out the indole-3-acetamide pathway (see Fig. 1), 2 while a fourth tryptophan-dependent pathway, via indole-3-acetaldoxime (see Fig. 1), is thought not to operate outside the Brassicaceae.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Recent metabolism experiments demonstrated that 4-Cl-IAA is synthesized via a chlorinated version of the indole-3-pyruvate pathway, the main tryptophan-dependent IAA synthesis pathway operating in pea seeds. 4 The growth regulatory role of chlorinated auxin is thought to involve the induction of GA biosynthesis and the inhibition of ethylene action on early pericarp growth and elongation. 5 The phylogenetic distribution and evolutionary origins of this hormone, however, have received little attention.…”
Section: Introductionmentioning
confidence: 99%